A mixed-methods study of emotional support for families of organ donors in Hunan Province, China - Xie, Wenzhao; Kong, Shufeng; He, Haiyan; Xiong, Huan; Zhu, Qizhen; Huang, Panhao (Frontiers in Psychology, 2022)
Background: Family consent is a prerequisite for deceased organ donation in China. However, a large number of donors are individuals who died due to accidental injuries or unanticipated diseases, which means that most of families of donors have just experienced the sudden death of their loved one and have to make a donation decision in a short time. This decision may cause psychological stress and some psychological damage to donors’ relatives. In addition, cultural sensitivity also has largely caused the donors’ relatives inner conflicts and contradictions. And sometimes organ donation may still be stigmatized. However, have they received any emotional support and what are the emotional support needs of them? Therefore, this study aims to investigate the emotional support, influencing factors and needs of the family members of organ donors in Hunan Province, China. Method: This is a Mixed-Methods research that combines quantitative and qualitative research methods. A cross-sectional survey was conducted among 102 donor families using a questionnaire to investigate their emotional support status. To further understand their emotional support needs, 12 donor families participated in the semi-structured interview. Results: The results confirmed that: (1) A total of 67.7% of the 102 respondents received emotional support or psychological comfort. Thus, only a small number of respondents (31.4%) felt respected by the public. (2) Emotional support came mainly from immediate family members (73.91%), official organizations such as the Red Cross (43.48%). (3) Marital status、health status、occupation、coping styles can affect the emotional support of the donor families(P＜0.05). (4) Interview showed that the donors’ families need the emotional support and psychological aid from psychological professionals most. And they wish to receive the understanding and respect of the public. Conclusion: Most organ donor families received emotional support from family, Red Cross, and friends, but only a minority of donor families reported receiving respect from the public after donation. And donor families showed a strong need for emotional support and professional psychological aid institutions.